A Dynamic Modelling of Unemployment Insurance - Anton Abdulbasah Kamil (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2011)
The paper analysis the level of unemployment insurance beneficiaries. The model is allow for thesimultaneous determination of wages with feedback from excess supply. The analysis concentrates onthe flow of workers in and out of unemployment rather than on the net result, the level ofunemployment. It focuses on the sub-set of the labor force covered by the unemployment insurance (UI)scheme. The estimation result show that the entry and exit rates exhibit some degree of persistence.Structural change effect both flow equations adversely. Real wages appear to be determined by a mix ofefficiency wage and market clearing factors.